Molecular identification of carnivore chaphamaparvovirus 2 (feline chaphamaparvovirus) in cats with diarrhea from China - Cui, Hao; Zhang, Zhibin; Xu, Xin; Zuo, Kejing; Ji, Jun; Guo, Ge; Kan, Yunchao; Yao, Lunguang; Xie, Qingmei; Bi, Yingzuo (Frontiers in Veterinary Science, 2023)
Chaphamaparvovirus carnivoran2 (Feline chaphamaparvovirus, FeChPV) is a novel feline parvovirus originally detected in Canadian cats in 2019, and it has also been identified in domestic cats in other nations. To evaluate the prevalence and genetic diversity of FeChPV in China, rectal swabs of pet cats from Henan, Guangdong, Anhui, Zhejiang, and Inner Mongolia provinces were collected. Of the 230 samples subjected to nested polymerase chain reaction, 6 (2.6%) tested positive for FeChPV. Although all positive samples were from cats with diarrhea, statistical analyses revealed no correlation between the presence of the virus and clinical symptoms (p > 0.05). Phylogenetic trees of nonstructural protein 1 (NS1) and capsid protein (VP1) demonstrated that these six new strains formed a major branch with other reference FeChPV strains and considerably differed from Chaphamaparvoviru carnivoran1. Moreover, recombination analysis revealed that the FeChPV strain CHN20201025, previously detected in a dog, was a recombinant and strains CHN200228 and CHN180917, identified in this study, were the closest relatives to the parental strains. The findings of this study and a previous study wherein FeChPV was detected in dogs suggest that FeChPV can propagate between species. Additionally, these findings indicate that the genetic diversity of FeChPV can provide an insight into the epidemiological status of FeChPV in China.